Emotions affect the recognition of hand gestures - Vicario, Carmelo M.; Newman, Anica (Frontiers in Human Neuroscience, 2013)
The body is closely tied to the processing of social and emotional information. The purpose of this study was to determine whether a relationship between emotions and social attitudes conveyed through gestures exists. Thus we tested the effect of pro-social (i.e. happy face) and anti-social (i.e. angry face) emotional primes on the ability to detect socially relevant hand postures (i.e. pictures depicting an open/closed hand). In particular, participants were required to establish, as quickly as possible, if the test stimulus (i.e. a hand posture) was the same or different, compared to the reference stimulus (i.e. a hand posture) previously displayed in the computer screen. Results show that facial primes, displayed between the reference and the test stimuli, influence the recognition of hand postures, according to the social attitude implicitly related to the stimulus. We found that perception of pro-social (i.e. happy face) primes resulted in slower RTs in detecting the open hand posture as compared to the closed hand posture. Vice-versa, perception of the anti-social (i.e. angry face) prime resulted in slower RTs in detecting the closed hand posture compared to the open hand posture. These results suggest that the social attitude implicitly suggested by the displayed stimuli might represent the conceptual link between emotions and gestures.